Literature Review: Rationality of Oral Antidiabetic Drug Administration in Type 2 Diabetes Mellitus Patients - Alicia Rahma, Cinta; Zakiah Oktarlina, Rasmi; Muhammad Aditya, Muhammad Aditya; Berawi, Khairun Nisa (Medula, 2024)
Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia due to problems with insulin performance, with prevalence continuing to increase throughout the world. According to Bodke et al (2023), in the last three decades, the number of diabetes sufferers is estimated to reach 642 million in 2040, with the majority being in low and middle income countries. Type 2 diabetes mellitus is the most common form, caused by insulin resistance and insufficient insulin secretion so that the sugar that enters the body is difficult to process. Management of diabetes mellitus requires a comprehensive approach that includes diabetes patient education, lifestyle changes, a balanced diet, and physical activity. Patient education is essential to increase their understanding of the disease and how to manage their health condition. Lifestyle changes and a balanced diet can help regulate blood glucose levels, while physical activity plays a role in improving insulin sensitivity. Antidiabetic drugs consist of oral and injectable preparations. The combination of pharmacological therapy with oral antidiabetic drugs such as metformin and SGLT2 inhibitors has also proven effective in lowering blood glucose levels and reducing the risk of complications. This approach is expected to improve the quality of life of diabetes mellitus patients and reduce the burden of disease in society. This literature review aims to explore the importance of rationality in administering antidiabetic drugs to type 2 diabetes mellitus patients in Indonesia.